Elevated urine oxalate and renal calculi in a classic galactosemia patient on soy‐based formula. Issue 1 (21st June 2019) - Sabatino, Julia A.; Starin, Danielle; Tuchman, Shamir; Ferreira, Carlos; Regier, Debra S.
Abstract: Classic galactosemia results from a deficiency in the galactose‐1‐phosphate uridylyltransferase (GALT) enzyme, which is essential for galactose metabolism. Treatment focuses on lactose restriction and is achieved with a soy‐based diet. Previously, renal calculi have not been documented in galactosemia patients. We present a patient with galactosemia nutritionally dependent on soy‐based formula via G‐tube, who developed renal calculi. Analysis of urinary stone risk factors revealed elevated urine oxalate levels and stone analysis confirmed calcium oxalate composition. Initiation of lactose‐ and soy‐free elemental formula returned urine oxalate level to normal. Given the presence of a metabolic pathway for the conversion of galactose to oxalate, and the high content of oxalate in soy‐based formula, there is the potential for elevated urine oxalate and a resulting risk of urinary calculi formation in patients with classic galactosemia. This potential can be effectively managed with a lactose and soy‐free elemental diet. This report describes the clinical course and novel findings of calcium oxalate urinary calculi in a classic galactosemia patient dependent upon soy‐based formula, with a discussion regarding the multiple factors leading to increased stone formation in this patient.